2014
DOI: 10.1186/1471-2474-15-363
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation and brace fixing for the treatment of congenital clubfoot in newborns and infants

Abstract: BackgroundAs one of the most common congenital deformities in children, clubfoot has long been a challenge for orthopedic surgeons. This paper describes the experience of our team with manipulation and above-the-knee brace fixation without percutaneous Achilles tenotomy for the treatment of clubfoot in newborns and infants.MethodsIn the orthopedic department of our hospital, 32 infants and newborns (56 feet) with congenital clubfoot underwent manipulation and above-the-knee brace fixation between 2008 and 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
0
7
0
4
Order By: Relevance
“…Corroborating these findings and reinforcing the indication of lighter braces, Su and Nan (2014) demonstrated that immobilizing newborns in the conservative treatment of CC can be achieved by more flexible devices. Su and Nan (2014) attached a Velcro strap above the newborn's knee as a therapeutic strategy. The authors treated 56 feet and 52 achieved normal appearance within 3 to 6 months of treatment.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Corroborating these findings and reinforcing the indication of lighter braces, Su and Nan (2014) demonstrated that immobilizing newborns in the conservative treatment of CC can be achieved by more flexible devices. Su and Nan (2014) attached a Velcro strap above the newborn's knee as a therapeutic strategy. The authors treated 56 feet and 52 achieved normal appearance within 3 to 6 months of treatment.…”
Section: Discussionmentioning
confidence: 62%
“…It seems that strong, lightweight noninvasive tools, such as that used here, are very promising in the conservative treatment of CC in the neonatal phase (BOECHAT et al, 2012;SU;NAN, 2014). During this phase of life, handling objects, exploring the environment and relating with people are essential tasks for developing autonomy (SANTANA; BRAGA, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our experience suggests that the newly designed braces solve these problems. Our experience also suggests that the earlier we started the treatment, the better results we could obtain [11].…”
Section: Discussionmentioning
confidence: 99%
“…Plaster casting is an essential part of this treatment [10]. We recently developed a simple brace for use in newborns and infants that produced excellent results [11]. We developed a second-generation brace with three polyaxial joints that can be easily adjusted for proper foot positioning after manipulation.…”
Section: Introductionmentioning
confidence: 99%